Work Fatigue Analysis on Gas Station Operators - Basri, Zaenal; Kalla, Ruslan; Alwi, Muhammad Khidri (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2021)
Background: Work fatigue is a complex criterion that not only concerns physiological and psychological fatigue but is dominantly related to decreased physical performance, feelings of fatigue, decreased motivation and decreased work productivity. The existence of this research is to see the relationship between work shift, stress, workload, working period, age, gender and work fatigue. Aim: This study aims to analyze the factors related to the Work Fatigue of Gas Station Operators in Makassar City in 2021. Methods: The type of research used is analytic with the Corss Sectional Study approach, which aims to see the relationship between two variables, namely the independent variable and the dependent variable. The population in this study were 62 operators from three gas stations in Makassar, where the first gas station was located at Sudiang Jl.Printis Kemerdekaan KM 16 Front of the Police, 7180277 totaled 20 operators, SPBU II 7490203 Jl.Sultan Hasanuddin Km 4.2 totaled 25 operators and gas station III 7490295 Jl. Talasalapang KM 3.7 Total 17 operators. Results: The results of this study showed that there was a significant relationship between work fatigue at gas station operators (p value = 0.004) workload, (p value 0.001) work stress, (p value 0.003) age, (p 0.005) years of service, (p value 0.003) Gender (p value 0.660) Shift work. The author suggests Pertamina to pay attention to the condition of the operator while working. Conclusion: Years of service, length of work, history of disease, smoking habits, weight of burden, and repetitive activities have a significant relationship with complaints of musculoskeletal disorders in workers at CV. Guna Agung Makassar.